An Efficient Risk-Aware Distributed Control System to Minimize Routing Attacks on MANET - Dahekar, Swati M.; Bhute, Yogesh (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
The topological nature of MANET(Mobile Ad-hoc Network) itself demands high security due to its mobility movement, but designing a risk aware routing path for MANET is a complex task because of its Dynamic nature of Infrastructure. In this proposal, designing an Dynamic routing path decider to find less risk aware routing path for effective communication. The efficiency of the throughput and Routing failures can be further reduced by making Nodes of MANET to be more Knowledgeable that is with more Metadata parameters. This paper introduce a class of metrics to measure the effective security offered in a wireless network as a function of the routing topology and the link security provided by the key assignment protocol. This joint protocol analysis allows a network analyst or an adversary to evaluate the vulnerability of network traffic and isolate weakly secured connections. Its show how an intelligent adversary can mount a node capture attack using vulnerability evaluation to focus the attack on the nodes which contribute maximally to the compromise of network traffic.